Find the product mentally.
(2j + 7)(2j - 7)

Question

Asked 8/7/2016 4:33:07 PM

Updated 8/7/2016 11:34:30 PM

2 Answers/Comments

This answer has been confirmed as correct and helpful.

s

scorpionsheep|Points 100|

= (2m - 9)(2m - 9)

= 4m^2 - 36m + 81

Question

Asked 8/7/2016 4:33:07 PM

Updated 8/7/2016 11:34:30 PM

2 Answers/Comments

This answer has been confirmed as correct and helpful.

Rating

3

[(x + 1)(x - 1)]^2

= (x2 - 1) * (x2 - 1)

= x^4 - 2x^2 + 1

= (x2 - 1) * (x2 - 1)

= x^4 - 2x^2 + 1

Added 8/7/2016 11:33:56 PM

This answer has been confirmed as correct and helpful.

3

(a + 8)(b + 3) = ab + 3a + 8b + 24

Added 8/7/2016 11:34:15 PM

This answer has been confirmed as correct and helpful.

48j 5 k 2 ÷ (-3j 3 k)

Question

Not Answered

Updated 8/7/2016 10:57:53 PM

1 Answer/Comment

2x2 - 10x + 8 = 2(x - 1)(x - 4)

Added 8/7/2016 10:57:48 PM

This answer has been confirmed as correct and helpful.

Find the product mentally.
(ab + 3)(ab - 3) **Weegy:** (ab + 3)(ab - 3) = a^2b^2 - 3ab + 3ab - 9; = a^2b^2 - 9 (More)

Question

Updated 8/7/2016 11:32:22 PM

0 Answers/Comments

3a2 * 2a3 **Weegy:** 3a^2 * 2a^3 = 6a^5 **User:** Find the product.
a 4(3a 2 - 2a + 1) **Weegy:** a^4(3a^2 - 2a + 1) = a^4*3a^2 - a^4*2a + a^4 = 3a^6 - 2a^5 + a^4 **User:** -4x 3 y 2(7xy 4) **Weegy:** -4x^3y^2(7xy^4) = -28x^4y^6 **User:** Simplify (8m - 4n) + (6m + 3n). **Weegy:** (8m - 4n) + (6m + 3n)
= 8m - 4n + 6m + 3n;
= 14m - n **User:** Find the product.
-7(8 + k) **Weegy:** -7(8 + k)
(-7)(8) + (-7)(k)
= -56 - 7k **User:** Find the product.
3(m + n) (More)

Question

Not Answered

Updated 8/7/2016 11:42:20 PM

1 Answer/Comment

Simplify: 76 ÷ 72.

Question|Asked by kimmymunro2001

Updated 8/10/2016 9:54:59 PM

1 Answer/Comment

76 ÷ 72 = 19/18

Added 8/10/2016 9:54:59 PM

This answer has been confirmed as correct and helpful.

32,287,233

questions answered

There are no comments.